The Role of Sustainability Accounting in Enhancing Stakeholder Trust and Transparency - Purwanti, Ari; Pamungkas, Eko Wiji; Kartikaningrum, Sari; Ng, Suwandi; Nurcahaya, Claudya (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Sustainability accounting goes beyond the traditional financial reporting framework by encompassing non-financial information that significantly affects long-term business performance and societal welfare. This study employs a Literature Review methodology to critically analyze existing research on sustainability accounting's role in enhancing stakeholder trust and transparency. The literature review on "The Role of Sustainability Accounting in Enhancing Stakeholder Trust and Transparency" reveals that sustainability accounting is a critical mechanism for promoting corporate accountability, ethical behavior, and long-term stakeholder engagement. It facilitates transparent communication of environmental, social, and governance (ESG) practices, enabling stakeholders to make informed decisions based on reliable, non-financial information.